2016
DOI: 10.9734/ijtdh/2016/25292
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Disparities and Determinants of Nutritional Status of Under-Five Children: An Example of Akinyele Local Government Area, Ibadan

Abstract: Background: Nutrition is an important element of a child's survival and development. To achieve MDG 4 in Nigeria, nutritional status of under-five children needs to be improved as malnutrition remains an underlying factor in about one third of under-five deaths in Nigeria. Unfortunately, along with high prevalence of malnutrition, urban-rural disparities persist in child nutritional outcomes in Nigeria.Objective: To determine the differences in and predictors of the nutritional status of children in urban and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Also 16.4% and 9.0% of rural and urban children were stunted respectively. This higher prevalence of undernutrition among rural compared to urban children was also reported by Senbajo et al [ 18 ] and Ijarotimi et al [ 19 ] from southwest Nigeria, Tadesse et al [ 20 ] from Ethiopia and from other parts of sub-Saharan Africa and Asia as reported by UNICEF in her global report on nutrition 2016 [ 21 ]. Children from rural areas are socially disadvantaged with limited access to basic necessities of life including food and quality health care [ 21 ].…”
Section: Discussionsupporting
confidence: 75%
“…Also 16.4% and 9.0% of rural and urban children were stunted respectively. This higher prevalence of undernutrition among rural compared to urban children was also reported by Senbajo et al [ 18 ] and Ijarotimi et al [ 19 ] from southwest Nigeria, Tadesse et al [ 20 ] from Ethiopia and from other parts of sub-Saharan Africa and Asia as reported by UNICEF in her global report on nutrition 2016 [ 21 ]. Children from rural areas are socially disadvantaged with limited access to basic necessities of life including food and quality health care [ 21 ].…”
Section: Discussionsupporting
confidence: 75%
“…Sample Size determination was done using Pocock's sample size formula for comparing two proportions -also used by Ijarotimi et al [28,29].…”
Section: Sample Size Determinationmentioning
confidence: 99%